Using Hybrid Filter To Reduce Harmonics in Variable Speed Drive System - حويجي ريم; غسان حايك; نسمت أبو طبق (Latakia University Journal -Engineering Sciences Series, 2023)
The issue of harmonics is dangerous for the network and consumers because of its negative effects. This paper deals with the issue of eliminating harmonics by using hybrid filters. This research focused on hybrid filters because they are a combination of two filters with different structure and performance. The filter studied in this research consists of a parallel active filter connected to the common point with the network, where it is preceded on the network side by a passive filter (parallel capacitor) and followed by a passive filter (coil) on the load side. The main goal is to improve the performance of the filter using the hybrid type, and we have reached the results for this goal by modeling and simulation in the MATLAB program. A three-phase induction motor drive system, driven by direct torque control technology, has been modeled to operate in different modes such as acceleration, deceleration and braking. Then we analyzed the current and voltage harmonics, and due to the large harmonic distortion, a passive filter was initially added, so the distortion decreased to some extent. Then we added an active filter, which reduced distortion even further. Then we inserted the hybrid filter and got a better result than the previous two cases.